Integration of the TPACK model in the development of reading comprehension: A proposal for 7th year students of general basic education - Delgado Lucero​, ​Daniela Elizabeth; Méndez Ortega, ​Maritza Genoveva ​; Pozo Ordoñez, Álvaro Luis; Obando Eskola, Silvia Germania; Cunguán Guerra, Pablo Fernando (SATHIRI, 2025)
echnology advancements and the creation of new tools constantly shape the field of education. Globally, educators implement various educational strategies to enhance processes that teaching practice rapidly adapts to. To improve student learning performance across all knowledge domains, researchers are developing innovative models that expand exponentially. In this way, the students in Otavalo need to have technological, pedagogical, and content knowledge all incorporated into the TPACK model of education. This is why the research is focused on the seventh grade at the Unidad Educativa del Milenio Jatun Kuraka. It is a mixed-method study that uses exploratory, descriptive, and documentary methods to gather data from 77 students and/or teachers through surveys and interviews. Frequency scales are used to treat the data, which shows how important it is to quickly add technology to the classroom and train teachers on how to use it. It also shows the problems that had to be solved, like not having enough equipment and technical issues, so that the study could be finished. Lastly, the collected data was used to create a proposal that uses the TPACK educational model to teach reading comprehension. This led to the creation of a teaching guide that will assist teachers and students, improving students' academic performance and definitely making them better at decoding texts on their own.
Keywords: TPACK Model; reading comprehension; basic general education